EFEKTIVITAS METODE PEMBELAJARAN AKTIF TEKNIK CARD SORT DIBANDINGKAN DENGAN INDEX CARD MATCH TERHADAP KEMAMPUAN BAHASA JEPANG : kemampuan menulis Bahasa Jepang siswa kelas XI IPS SMAN Gunung Putri - Handayani; Nia Setiawati; Viana Meilani Prasetio (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2021)
Abstract: This study is research report about The Effectiveness of Active Learning Methods Card Sort Technique Compared with Index card match Technique on Japanese Language Ability on the high school students class at XI IPS SMAN 1 Gunung Putri. The research method is used true experimental method. The design is used pretest posttest control group design. The sample in this research is 30 students of class XI IPS 4 using card sort technique (experiment class) and 30 students of class XI IPS 1 using index card match technique (control class). After the posttest data was analyzed, card sort technique is more effective than index card match technique on Japanese language ability XI IPS class students.